ELEMENTARY TECHNIQUES OF BASIC HAND STROKES IN MODERN KARATE - Dragan Radovanović; Stevo Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The aim of this study is to explain in the best way possible the nature and significance of basic hand strokes in modern karate and the importance of their sensible application in combat as a means of achieving greater effectiveness. The object of the study is a theoretical demonstration of elementary techniques of performing basic hand strokes fit for use in combat with special attention to their practical application. The subject matter itself requires the use of a descriptive method. The paper will give a brief summary of the development of karate in our country and abroad, as well as a concise overview of the key principles of practicing karate techniques upon which the philosophy of karate as a martial art and sports discipline is based. The paper will also provide a systematization of hand techniques which are based on elementary hand strokes used most commonly owing to their effectiveness and practicability in karate combat, just one of the disciplines of modern karate.